Remarkable photoelectrochemical activity of titanium dioxide nanorod arrays sensitized with transition metal sulfide nanoparticles for solar hydrogen production. (December 2022) - Meshesha, M.M.; Kannan, K.; Chanda, D.; Gautam, J.; Jang, S.G.; Yang, B.L.
Abstract: The synthesis of a cost-effective and efficient catalyst is vital for accelerating the rate of photoelectrochemical hydrogen production. Here, titanium dioxide nanorods sensitized by nickel sulfide, cadmium sulfide, and zinc sulfide nanoparticles (ZnS/CdS/NiS@TiO2 ) were developed as a photoanode material via a hydrothermal process followed by the successive ionic layer adsorption and reaction. The morphological analysis of ZnS/CdS/NiS@TiO2 revealed the nanorods (TiO2 ) phase in which NiS, CdS, and ZnS nanoparticles are distributed homogeneously. The photoelectrochemical performance analysis of ZnS/CdS/NiS@TiO2 furnished a maximum photocurrent density of 6.1 mA/cm 2, which is 7.6 times higher than that of pure TiO2 (0.8 mA/cm 2 ). Additionally, the sensitized TiO2 nanorod arrays as a photoanode show high photoelectrochemical hydrogen production of 491.52 μmol/cm 2, which is 4.9 times higher than that of pristine TiO2 (99.61 μmol/cm 2 ) over 6 h under simulated solar irradiation. These results suggested the potential for the synthesis and usage of novel hybrids of TiO2 nanorods decorated with transition metal chalcogenides for efficient photoelectrochemical hydrogen production. Graphical abstract: Image 1 Highlights: Titanium dioxide nanorod sensitized by nickel sulfide, cadmium sulfide, and zinc sulfide nanoparticles (ZnS/CdS/NiS@TiO2 ) is reported first time for the photoelectrochemical (PEC) hydrogen production. ZnS/CdS/NiS@TiO2 delivered excellent activity and rate for PEC hydrogen generation. Accelerated charge transfer/hole separation is responsible for excellent activity. ZnS/CdS/NiS@TiO2 heterostructures offer far better performance in PECs than TiO2 .